If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + -3x = 48 Solving 1 + -3x = 48 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -3x = 48 + -1 Combine like terms: 1 + -1 = 0 0 + -3x = 48 + -1 -3x = 48 + -1 Combine like terms: 48 + -1 = 47 -3x = 47 Divide each side by '-3'. x = -15.66666667 Simplifying x = -15.66666667
| 4y=24+2x | | 1.2+0.3=7.5 | | 3d^2-d-4=0 | | 9x-48=x | | Cosx=cord | | 80-x=4x-30 | | 2x+y=560 | | x+25+2x-20=110 | | 4x-6+5x+15=180 | | 360-305= | | 90+90+125= | | 10x-48=180 | | 215+125= | | 215+65= | | 55+215= | | 360-215= | | 2x+10=108 | | 215-180= | | 11x-3x=48 | | 125+90= | | -4x=3+-2x+8 | | Logt=2.8 | | 100*log(x)=4 | | 100*log(x)=-1 | | p-3=6p-28 | | 100*log(x)=0 | | -3x+3=10x+15 | | x=(6x+12) | | 2(8a-6)-5=-145 | | 4x-10x+22= | | 3x+8-0.5x=16 | | -23+5(7-12x)=7(1-6x)-3(2x+1) |